Knowledge analisys of construction professionals about the civil construction and demolition waste in the city of Campo Mourão – PR - Simoni, Julio Henrique; Alencar, Jose Luciano Sobreira de; Fiorelli, Mariana Natale; Neto, Generoso De Angelis (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Recycling and re-use terms are commonly discussed due to the it’s importance in the sustainability in civil constructions in situations such as reduction of environmental impact as well as cost reduction. The companies which works with recycling has been gaining more market share by selling goods from civil construction, however note that the ideia of sustainability must be intensified for this market. Thus, the main objective of this article is to show a example of a company and its works with waste civil construction recycling in Maringá-PR city as well as how this has been making the application of sustainable means for generation raw material for sales to regional companies or even for use in their own establishments.